Navigare... - Jędrzejko, Paweł (Review of International American Studies, 2014)
Paweł Jędrzejko Institute of English Cultures and Literatures Faculty of Philology University of Silesia in Katowic Poland Navigare Navigare necesse est, vivere non est necesse. This sentence, attributed to Pompeius Magnus, has inspired humankind for generations. Whether it is interpreted literally or metaphorically, the imperative expresses the absolute necessity of movement—irrespective of its motivation—as a condition of the existence of a future. Yet, navigation cannot be simply reduced to movement alone: after all, those who navigate differ from those who are adrift in their ability to actively control their course. As an intentional form of movement, navigation is, in a sense, synonymous to negotiation: to negotiate one’s way through rocks and shoals, one needs to simultaneously demonstrate stamina, sensitivity, and vast knowledge. The mastery of the vessel, its structure, handling, maintenance and maneuverability must go hand in hand with the knowledge of meteorology, trigonometry, cartography, and many other areas of applied science. Still, such knowledge alone may not suffice to make port safely. Ships need crews, and thus the navigator must negotiate the ship’s course in yet another dimension: pushing the limits of his or her fellow sailors to warrant the vessel’s survival, the navigator must know when and how to let go to avoid a catastrophe. On board, everyone needs everybody else because everybody depends on everyone else. Importantly, no seafarer should ever forget that a ship is not a discursive structure: it cannot be deconstructed, it cannot be relativized. Its continued existence depends on how well it is maintained and how efficiently it is managed. Navigation is thus is both a complex craft and a subtle art, it requires training, experience and an acute awareness of one’s own limitations and the limitations of those with whom one interacts. A navigator is first and foremost a reader and an interpreter: as the reader of the sea, the skies, the landmarks, the reader of the movement of the craft, he or she is also an interpreter of a multitude of languages and other forms of expression in his or her negotiations with people. Navigation, therefore, is a multifaceted challenge. Driven by our future projects, we are all in motion. Individually or in small crews, we constantly negotiate our courses, changing headings when necessary, and constantly learning. Still, the longer we sail the liquid expanse of our ever-changing reality, the more palpable our realization of our common condition becomes. Struggling, loving, worrying, joying, mourning, celebrating—we may live in different forecastles, but we really sail the same ship: a multilingual crew of navigators, more and more aware of the fact that we merely seem to be worlds apart. Eliminate the ‘l’ through learning and empathy—and the rest is negotiation of the shared space. And negotiate we must: of course, vivere non est necesse, but with us, or without us, the world/word will go on. Navigators ourselves, as teachers and thinkers we have a rare opportunity to train others in hope that the ship of humankind does not turn out to be the Ship of Fools or the Pequod, and that we do not end up in The Raft of the Medusa. We know that jumping ship is only possible when the ship has made port. Living our worrisome lives towards death, our final haven is always too far for us to consider any alternative to sailing on; responding to the universal thump that life democractically gives us, we may choose to follow Melville and negotiate the universal squeeze of the hand instead. Because navigare necesse est. Quod erat demonstrandum. Paweł Jędrzejko RIAS Associate Editor